Fundamentals and key components of sodium-ion batteries: Challenges and future perspectives - Suntharam N.M.; Bashir S.; B V.; Rahim N.A.; S R.; Ramesh S.; Ramesh K.; Prasankumar T. (Elsevier Ltd, 2025)
Energy storage systems play a pivotal role in modern society by addressing the intermittent nature of renewable energy sources and enhancing grid stability. Among these systems, rechargeable batteries stand out as a key technology to provide efficient and portable energy storage solutions. As a buffer to balance variations in supply and demand, rechargeable batteries store electrical energy during times of surplus generation or low demand and release it when needed. These batteries are made up of electrochemical cells, which store and release electrical energy through reversible processes. A common type of rechargeable battery is lithium-ion battery (LIB) which is widely utilized in portable electronics and electric vehicles. But the expense and scarcity of lithium supplies forced scientists to investigate other materials, which brought them to study sodium-ion chemistry, reflecting a pursuit for development of alternative sodium-ion batteries (SIBs). The advent of SIBs represents a paradigm change in the field of energy storage, showcasing creativity and flexibility in response to the changing needs of a more sustainable and easily obtainable energy supply. Here, electrodes act as crucial element in SIBs and therefore, electrodes must be developed with high compatibility and stability to ensure good performance in SIBs. Recently, transition metal oxides, Prussian blue analogues, polyanionic compounds and organic materials have been investigated as cathode materials for SIBs. In unison, latest progressions have been done to fabricate many anode materials such as carbon-based materials, alloy-based compounds, MXenes, metal oxides and sulfides and organic compounds. Concurrently, many modifications have been made to enhance the performance and stability of electrode materials in the battery systems. Apart from that, many electrolytes have been widely investigated for SIBs to enhance the performance, efficiency and safety features. To give insights into the structures and morphologies of the electrode materials as well as the electrochemical performance of the systems, various advanced characterization techniques have also been reviewed. In this article, we have outlined and exchanged views on the research materials that have been explored and proposed future perspectives for SIBs. This review offers crucial insights into practical and scientific problems related to the evolution of SIBs. ? 2024 Elsevier Ltd